2015
DOI: 10.1161/circulationaha.114.010637
|View full text |Cite
|
Sign up to set email alerts
|

Phenomapping for Novel Classification of Heart Failure With Preserved Ejection Fraction

Abstract: Introduction Heart failure with preserved ejection fraction (HFpEF) is a heterogeneous clinical syndrome in need of improved phenotypic classification. We sought to evaluate whether unbiased clustering analysis using dense phenotypic data (“phenomapping”) could identify phenotypically distinct HFpEF categories. Methods and Results We prospectively studied 397 HFpEF patients and performed detailed clinical, laboratory, electrocardiographic, and echocardiographic phenotyping of the study participants. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
798
1
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 861 publications
(840 citation statements)
references
References 26 publications
31
798
1
10
Order By: Relevance
“…A prospective study is needed to determine whether the same medical therapies (renin‐angiotensin aldosterone system inhibitors and beta‐blockers) that have efficacy for reducing progression to symptomatic HF in patients with asymptomatic LV systolic dysfunction would also have comparable efficacy in patients with malignant LVH. Recently, it has been suggested that it is possible to subgroup HFpEF into different phenotypes using machine learning or other algorithms 23, 24. It remains to be determined whether the malignant LVH phenotype may be also able to identify specific patient phenotypes that would be at greater risk to progress to HFpEF among the overall heterogeneous HFpEF cohort.…”
Section: Discussionmentioning
confidence: 99%
“…A prospective study is needed to determine whether the same medical therapies (renin‐angiotensin aldosterone system inhibitors and beta‐blockers) that have efficacy for reducing progression to symptomatic HF in patients with asymptomatic LV systolic dysfunction would also have comparable efficacy in patients with malignant LVH. Recently, it has been suggested that it is possible to subgroup HFpEF into different phenotypes using machine learning or other algorithms 23, 24. It remains to be determined whether the malignant LVH phenotype may be also able to identify specific patient phenotypes that would be at greater risk to progress to HFpEF among the overall heterogeneous HFpEF cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In medicine, these methodologies can use a data‐driven approach to re‐examine phenotyping of complex diseases such as HF 11. Recently, these methods identified distinct phenotypes of HF with reduced and preserved ejection fraction (HFrEF and HFpEF) among 1619 patients with HFrEF enrolled in the HF‐ACTION (Heart Failure: A Controlled Trial Investigating Outcomes of Exercise Training) clinical trial and 397 patients seen at the HF clinic at outpatient clinic of the Northwestern University HFpEF Program 12, 13…”
Section: Introductionmentioning
confidence: 99%
“…The recently updated 2016 European Society of Cardiology (ESC) guidelines mandate an elevated brain natriuretic peptide (BNP) or N‐terminal pro‐BNP (NT‐proBNP) to diagnose HF, departing from prior recommendations 1, 2, 3, 4, 5…”
Section: Introductionmentioning
confidence: 99%